'A lockdown facility … with the feel of a small, private college': Liberal politics, jail expansion, and the carceral habitus. (February 2013) - Schept, Judah
While scholarship has identified neoliberalism, punitive and racialized public policy, and a supportive culture of punishment as giving rise to mass incarceration in the United States, little work has examined how communities come to participate in the production of the carceral state. Using an ethnographic case study of a proposed 'justice campus', a carceral expansion project in a politically progressive Midwestern city, this article illuminates the capacity of mass incarceration to structure individual and community dispositions and, in doing so, to imbue even oppositional politics. At the same time, communities may adopt, reformulate, and rearticulate the symbolic work and material manifestations of mass incarceration in order to fit specific political-cultural contexts. As such, this article argues that mass incarceration is both more forceful and more subject to diverse and context-specific formulations than has been previously argued. The corporal and discursive inscription of carcerality into individual and community bodies suggests the presence of a carceral habitus and offers one way to comprehend not only mass incarceration's pervasive presence, but also its hegemonic operations even among and through people and communities who purport to reject it.